2017
DOI: 10.1111/jop.12654
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived exosomes enhance invasion and metastasis of salivary adenoid cystic carcinoma cells

Abstract: The results suggested that SACC cell-derived exosomes were loaded with individual components that could enhance invasiveness and induce microenvironment changes, thus promoting SACC aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This indicates that interventions targeting exosome biogenesis and release may be of therapeutic value against PNI ( 92 ). Of particular note, in our previous study, we found that the exosomes derived from the adenoid cystic carcinoma cell line (SACC-83) could be uptaken by human umbilical vein endothelial cells (HUVECs), and destroyed the vascular endothelial barrier ( 93 ). Considering that primary tumor-derived EVs can destroy epithelial cell tight junction assembly to induce EMT, and trigger vascular permeability to allow cancer cell dissemination, and “educate” pre-metastatic sites in distant organs, we propose that EVs may also contribute to the disruption of the perineurium barrier and education of the perineural sites into a tumor-promoting microenvironment.…”
Section: Possible Mechanism Of Pni and Conclusionmentioning
confidence: 98%
“…This indicates that interventions targeting exosome biogenesis and release may be of therapeutic value against PNI ( 92 ). Of particular note, in our previous study, we found that the exosomes derived from the adenoid cystic carcinoma cell line (SACC-83) could be uptaken by human umbilical vein endothelial cells (HUVECs), and destroyed the vascular endothelial barrier ( 93 ). Considering that primary tumor-derived EVs can destroy epithelial cell tight junction assembly to induce EMT, and trigger vascular permeability to allow cancer cell dissemination, and “educate” pre-metastatic sites in distant organs, we propose that EVs may also contribute to the disruption of the perineurium barrier and education of the perineural sites into a tumor-promoting microenvironment.…”
Section: Possible Mechanism Of Pni and Conclusionmentioning
confidence: 98%
“…Exosomes containing EGFR from OSCC cells were capable of transforming normal epithelial cells into a mesenchymal phenotype in a paracrine fashion [17]. Hou et al found that exosomes from salivary adenoid cystic carcinoma cell line SACC-83 enhanced the migration and invasion ability of the parental SACC-83 by targeting cell junction-associated proteins, including claudin-1, ZO-1, and β-catenin [16,39].…”
Section: Proteins In Oscc Cell-derived Exosomesmentioning
confidence: 99%
“…Recent studies have revealed the multifaceted roles of exosomes in oral diseases. Oral cancer-derived exosomes exacerbated the malignancy of cancers [16][17][18][19]. Li et al proved the hypoxic oral squamous cell carcinoma (OSCC) cells secreted miR-21-rich exosomes in a HIFdependent manner [20].…”
Section: Introductionmentioning
confidence: 99%
“…By artificially mimicking the OSCC TME (arranging tumor cells in a three-dimensional myoma or collagen gel model), it was found that tumor-derived exosomes play an important role in regulating tumor epithelial morphology and function [69]. Exosomes could promote the formation of tumor epithelial islands and of the expression of interstitial cell characteristics, such as upregulating N-cadherin, downregulating E-cadherin and GLI-1, and eventually promoting the epithelial-mesenchymal transition (EMT) [70, 71]. Shinya Sento et al demonstrated that OSCC-derived exosomes can self-uptake or become absorbed by surrounding tumor cells and then accelerate cell proliferation and invasion by activating AKT, MAPK/ERK, and JNK signaling pathways [72].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nasopharyngeal carcinoma (NPC) cell-derived exosomal miRNA-23a directly target the TSGA10 region to promote endothelial cell proliferation, migration and tube formation to regulate tumor growth [97]. Recent studies have shown that epiegulin-, MMP-13-, ICAM-1- or TSP-1-enriched exosomes could strengthen the release of vascular endothelial growth factors (VEGF-A, FGF-2, IL-8) and then downregulate junction-related proteins (claudins and ZO-1) that promote tumor angiogenesis and vascular permeability, becoming a potential passway system for distant metastasis of tumor cells [70, 71, 73, 98].…”
Section: Introductionmentioning
confidence: 99%